Madness and Kant’s Philosophy: The Importance of Philosophy to Medicine - Failla, Mariannina (Con-Textos Kantianos. International Journal of Philosophy, 2021)
The introduction to the Dossier on mental disorder in the work of Kant considers the relationship between philosophy and medicine. Its brief suggestions are linked to only one form of pathology: hypochondria, on the one hand; and a highly particular aspect of mental disorder: its relationship with criminal accountability or, if we wish, the legitimacy of punishment, on the other hand.